2023
DOI: 10.3390/antiox13010053
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Supplementation Improves Oocyte Development by Modulating Mitochondria and Yolk Protein in a Caffeine-Ingested Caenorhabditis elegans Model

Hyemin Min,
Mijin Lee,
Sangwon Kang
et al.

Abstract: Vitamin B12 is an essential cofactor involved in the function of two enzymes: cytosolic methionine synthase and mitochondrial methylmalonic-CoA mutase. In our previous studies, caffeine (1,3,7-trimethylxanthine), the most popular bioactivator, was shown to reduce yolk protein (vitellogenin) and fertility in a Caenorhabditis elegans model. Based on the previous finding that methionine supplementation increases vitellogenesis in C. elegans, we investigated the role of vitamin B12 in methionine-mediated vitelloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…We previously showed that the decrease in reproduction and vitellogenesis caused by caffeine intake was improved by vitamin B12 supplementation, which acts as a co-factor in the Met/SAM cycle in C. elegans [ 34 ]. Considering the important role of methionine in cellular metabolism, we investigated its role in reproduction in caffeine-ingested animals (CIAs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that the decrease in reproduction and vitellogenesis caused by caffeine intake was improved by vitamin B12 supplementation, which acts as a co-factor in the Met/SAM cycle in C. elegans [ 34 ]. Considering the important role of methionine in cellular metabolism, we investigated its role in reproduction in caffeine-ingested animals (CIAs).…”
Section: Resultsmentioning
confidence: 99%
“…We found that caffeine intake significantly reduced methionine levels and vitellogenesis and, thus, increased germ cell apoptosis. Recently, it has been reported that maternal caffeine intake causes mitochondrial stress in the germ line of C. elegans [ 34 ], but the mechanism by which caffeine intake induced mitochondrial stress in the germline remains unclear. Interestingly, some studies have demonstrated an interrelationship between methionine metabolism and mitochondrial function with direct relevance [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%